2016
DOI: 10.1158/0008-5472.can-16-0810
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2 Signaling Drives the Development and Progression of Pancreatic Cancer

Abstract: mTOR signaling controls several critical cellular functions and is deregulated in many cancers, including pancreatic cancer. To date, most efforts have focused on inhibiting the mTORC1 complex. However, clinical trials of mTORC1 inhibitors in pancreatic cancer have failed, raising questions about this therapeutic approach. We employed a genetic approach to delete the obligate mTORC2 subunit Rictor and identified the critical times during which tumorigenesis requires mTORC2 signaling. Rictor deletion resulted i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 56 publications
6
73
0
1
Order By: Relevance
“…Previous studies have revealed that rapamycin therapy for PC patients was not effective and the efficacy of metformin in vivo was contradictory in many studies (30)(31)(32)(33)(34)(35)(36). The present study demonstrated the anti-tumor action of metformin and revealed the synergistic action of metformin and rapamycin in the treatment of PC cells by the downregulation of the mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have revealed that rapamycin therapy for PC patients was not effective and the efficacy of metformin in vivo was contradictory in many studies (30)(31)(32)(33)(34)(35)(36). The present study demonstrated the anti-tumor action of metformin and revealed the synergistic action of metformin and rapamycin in the treatment of PC cells by the downregulation of the mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 54%
“…48 However, studies in mice brought to evidence the important role of mTORC2 signaling in pancreatic tumorigenesis and suggest that dual mTORC1/2 inhibition might be promising. 49 Our data from human PC tumors showed an association between tumor budding and other adverse histologic features as adjacent organ and vein invasions. Interestingly, our data also provided a trend between the presence of tumor budding and high expression of ZEB-1.…”
Section: Discussionmentioning
confidence: 64%
“…The combination therapy of capecitabine (a prodrug of 5‐fluorouracil) and everolimus only showed a modest improvement in a phase II clinical trial as first‐line or second‐line treatment of PC . However, studies in mice brought to evidence the important role of mTORC2 signaling in pancreatic tumorigenesis and suggest that dual mTORC1/2 inhibition might be promising …”
Section: Discussionmentioning
confidence: 99%
“…This may further be explained by mTORC1 being involved in complex negative feedback loops that restrain upstream signalling. More recently developed dual ATP-competitive agents that target mTORC1/mTORC2 have shown favourable results [207,208] with AZD2014 effectively inhibiting PDAC cell division (G1 arrest), proliferation, and invasion in vitro [158,160] and prolonging survival in the KPC mouse model of PDAC [109,208,209]. More recently developed dual ATP-competitive agents that target mTORC1/mTORC2 have shown favourable results [207,208] with AZD2014 effectively inhibiting PDAC cell division (G1 arrest), proliferation, and invasion in vitro [158,160] and prolonging survival in the KPC mouse model of PDAC [109,208,209].…”
Section: Modulation Of the Upstream And Downstream Src Signalling Commentioning
confidence: 99%
“…For example, inhibition of mTORC1 drives activation of PI3K-, AKT-or ERK pathways [205], which in turn limits the efficacy of mTORC-inhibitors as targeted therapies [206]. More recently developed dual ATP-competitive agents that target mTORC1/mTORC2 have shown favourable results [207,208] with AZD2014 effectively inhibiting PDAC cell division (G1 arrest), proliferation, and invasion in vitro [158,160] and prolonging survival in the KPC mouse model of PDAC [109,208,209]. However there is still some debate as to whether blocking mTORC1/2 leads to the adaptive activation of the PI3K-AKT pathway [209], and consequently whether multiple targeting of this network is required to effectively interfere with both branches of adaptive signalling and to elicit a durable therapeutic response.…”
Section: Modulation Of the Upstream And Downstream Src Signalling Commentioning
confidence: 99%